2002
DOI: 10.1073/pnas.202301299
|View full text |Cite
|
Sign up to set email alerts
|

Classification of scale-free networks

Abstract: While the emergence of a power-law degree distribution in complex networks is intriguing, the degree exponent is not universal. Here we show that the betweenness centrality displays a powerlaw distribution with an exponent , which is robust, and use it to classify the scale-free networks. We have observed two universality classes with Ϸ 2.2(1) and 2.0, respectively. Real-world networks for the former are the protein-interaction networks, the metabolic networks for eukaryotes and bacteria, and the coauthorship … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
193
1
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(211 citation statements)
references
References 33 publications
9
193
1
2
Order By: Relevance
“…Load, independently of search, has been analyzed in different classes of networks [28][29][30][31]. The load, as introduced in these works, is equivalent to the betweenness as it has been defined in social networks [32,28].…”
Section: Load and Congestion In Complex Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Load, independently of search, has been analyzed in different classes of networks [28][29][30][31]. The load, as introduced in these works, is equivalent to the betweenness as it has been defined in social networks [32,28].…”
Section: Load and Congestion In Complex Networkmentioning
confidence: 99%
“…On the other side, the load distribution of small-world networks shows a combined behavior of two Poisson-type decays. In subsequent work, the authors in [31] suggested that real-world networks should be classified in two different universality classes, according to the exponent of the power-law distribution of loads. Finally, the distribution of loads was analytically computed for scale-free trees in [30].…”
Section: Load and Congestion In Complex Networkmentioning
confidence: 99%
“…For the purpose of working path computations, we propose to use the metric based on the so called betweenness centrality parameter (BC) defined in [10] and shown in (2), since it provides us with good estimates on the centrality of node n, and therefore on its vulnerability to attacks.…”
Section: Proposed Approachmentioning
confidence: 99%
“…(2) [17]. The Internet AS map is no exception and the load exponent δ of the power law is estimated to be approximately δ ≈ 2.0 [17,18].…”
Section: Load Distribution Of Internetmentioning
confidence: 99%
“…(2) [17]. The Internet AS map is no exception and the load exponent δ of the power law is estimated to be approximately δ ≈ 2.0 [17,18]. The power-law load distribution means that a few ASes should handle an extraordinarily large amount of load while most others should do only a little.…”
Section: Load Distribution Of Internetmentioning
confidence: 99%